HUBUNGAN PENGETAHUAN DAN SIKAP IBU YANG MEMILIKI BAYI USIA 6-12 BULAN TERHADAP PEMEBERIAN ASI EKSKLUSIF DI PMB JUNILDA LHOKSEUMAWE ACEH UTARA TAHUN 2023 - Utary Dwi Listiarini; Indah Dewi Sari; Ani Deswita Chaniago; Sovia Eka Susanti (Universitas Prima Indonesia, 2023)
According to WHO in 2018, 42% of babies breastfed in the last hour and 41% of babies received exclusive breast milk until the age of 6 months. Exclusive breastfeeding for babies can reduce the death rate by less than 800,000 babies. According to RISKESDA 2018, 52.5 percent - or only half of the 2.3 million babies aged less than six months - receive exclusive breast milk in Indonesia. The aim of the research is to determine the relationship between knowledge and attitudes of mothers who have babies aged 6-12 months towards providing exclusive breast milk at Pmb Junilda Lhokseumawe, North Aceh in 2023. The design of this research is a quantitative analytical survey using a cross sectional study. The population in the study were all mothers who had babies aged 6-12 months in August at PMB Junilda Lhoksemawe, totaling 30 people and the sample used a total population of 30 mothers. The data used uses primary and secondary data. Data analysis used univariate and bivariate using the chi square test. The design of this research is a quantitative analytical survey using a cross sectional study. The population in the study were all mothers who had babies aged 6-12 months in August at PMB Junilda Lhoksemawe, totaling 30 people and the sample used a total population of 30 mothers. The data used uses primary and secondary data. Data analysis used univariate and bivariate using the chi square test.n The research results were obtained using the chi square test. There is a relationship between the mother's knowledge of having a baby 6-12 months and exclusive breastfeeding at Junilda Independent Practicing Midwives, Lhokseumawe City in 2023 with the chi-square statistical test p = 0.001 and there is a relationship between the attitude of the mother having a baby 6-12 months. 12 months with exclusive breastfeeding at Junilda Independent Practicing Midwives, Lhokseumawe City in 2023 with the chi-square statistical test p = 0.011.<0.05. The conclusion is that there is a relationship between the knowledge and attitudes of mothers who have babies 6-12 months with exclusive breastfeeding at Junilda Independent Practicing Midwives, Lhokseumawe City in 2023. It is hoped that Junilda Midwives will further improve prevention in order to prevent failure in exclusive breastfeeding and provide information in order to provide IEC to pregnant women, post partum to provide exclusive breastfeeding